Teori Konflik dan Perubahan Sosial: Sebuah Analisis Kritis - Asep Saefudin (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2005)
Conflict theory is born as reaction toward structural functional approach for social change analysis. This theory gained its popularity in 1960s, rooted in Max Weber concept of power conflict and Karl Marx’ theses focused on economy conflict. This article emphasized Marx concept concerning social change which is frequently used in conflict argumentation. Although widely used for social analysis, Marx theory has weaknesses, too. Ritzer and Goodman described some critics toward Marxian approach: (1) failed to prove social revolution; (2) unable to comprehend capitalist system flexibilities; (3) too radical; (4) ideological-biased; and (5) unable to prove the success of Marxist-Communist states.